UNDERSTANDING THE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) MODEL IN MAHARATUL KITABAH LEARNING: AN EFFECTIVENESS ANALYSIS THROUGH THE ARABICVERSE TEXTBOOK AT FATHONA PAKJO PALEMBANG JUNIOR HIGH SCHOOL - Annisa Shabrina; Nurul Hidayah; Jamanuddin Jamanuddin (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study analyzes the effectiveness of the Student Team Achievement Division (STAD) model in teaching maharatul kitabah (Arabic writing skills) at Fathona Pakjo Palembang Junior High School using a mixed-methods approach, combining both quantitative and qualitative methods. The quantitative approach involves descriptive analysis to evaluate students' learning outcomes before and after implementing the STAD model. In contrast, the qualitative approach explores students' and teachers' experiences during the learning process. Data were collected through observations, interviews with teachers and students, and an analysis of instructional documents. The findings indicate that implementing the STAD model significantly enhances students' understanding of Arabic language structures and their writing skills. Additionally, the use of the Arabicverse textbook as a teaching resource supports the learning process by providing systematic and practice-based materials. The most prominent keywords in this study are learning, the STAD model, and Arabicverse. These findings have significant implications for developing Arabic language teaching strategies at the secondary school level, particularly in utilizing cooperative learning methods to improve students' writing skills